Pengaruh Ketrampilan Kerja Terhadap Kinerja Karyawan Yang Dimediasi Oleh Beban Kerja Pada Usaha Kerajinan Tas Aceh Di Ulee Madon - Yusniar Yusniar; Heriyana Heriyana; Nurlaili Nurlaili (Jurnal Visioner & Strategis, 2021)
This study aims to analyze the effect of skills on employee performance mediated by workload in the Acehnese bag craft business in Uleu Madon. The sample in this study was 98 respondents using path analysis. The data used in this study are primary and secondary data. The results showed that both work skills as well as workload affect employee performance. The results of the path analysis show that work skills can have a direct effect on performance and can also have an indirect effect, namely from work skills to workload and then to performance.